MISKONSEPSI SISWA SMP DALAM MEMAHAMI KONSEP BANGUN DATAR - Rafik Asril; Agustin Fatmawati (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
The purpose of this study is to describe the misconceptions of flat shapes experienced by students at the elementary school level and provide alternative solutions to understand students' concepts of flat shapes. The method used is a literacy study by referring to sources such as books, articles, and journals. The results obtained regarding students' misconceptions about the concept of flat shapes are 1) there is no difference between concepts and numbers; 2) value of = 22/7 ; 3) parallelograms, rhombuses and squares are not rectangles. Alternative solutions offered to understand students about the concept of flat shapes include 1) re-explaining or re-explaining part of each concept or procedure; 2) problem student thinking or asking students to explain how they solve problems; 3) cognitive conflict, namely managing mathematics learning situations that allow elementary school students to identify conflicting mathematical principles between the original answers and students' answers.